Clinical features, angio-architectural phenotypes, and treatment strategy of foramen magnum dural arteriovenous fistulas: a retrospective case series study - Xiao, Zhipeng; Gao, Weizhen; Zhou, Hongyu; Zhang, Xiaohua; Dai, Jiong; Wan, Jieqing; Guo, Liemei (Frontiers in Neurology, 2023)
Background The rarity and complex angioarchitecture of foramen magnum dural arteriovenous fistulas (DAVFs) make its treatment difficult and controversial. We aimed to describe their clinical features, angio-architectural phenotypes, and treatments, through a case series study. Methods We first retrospectively studied cases of foramen magnum DAVFs treated in our Cerebrovascular Center, and then reviewed the published cases on Pubmed. The clinical characteristics, angioarchitecture, and treatments were analyzed. Results A total of 55 patients were confirmed with foramen magnum DAVFs, which included 50 men and 5 women, with a mean age of 52.8 years. Most patients presented with subarachnoid hemorrhage (SAH) (21/55) or myelopathy (30/55), depending on the venous drainage pattern. In this group, 21 DAVFs were supplied by only the vertebral artery (VA), three by only the occipital artery (OA), three by only the ascending pharyngeal artery (APA), and the remaining 28 DAVFs were supplied by two or three of these feeding arteries. Most cases (30/55) were treated with only endovascular embolization, 18 cases (18/55) with only surgical disconnection, five cases (5/55) with combined therapy, and two cases rejected treatment. The angiographic outcome of complete obliteration was achieved in most patients (50/55). In addition, two cases of foramen magnum DAVFs were treated by us in a Hybrid Angio-Surgical Suite (HASS) with good outcomes. Conclusions Foramen magnum DAVFs are rare and their angio-architectural features are complicated. The treatment option (microsurgical disconnection or endovascular embolization) should be weighed carefully, and combined therapy in HASS could be a more feasible and less invasive treatment option.